Bovine salmonellosis and the challenge of developing cross protective vaccines for this disease - Engels, Justin Allen (Kansas State University, 2017)
Salmonella contamination of meat is a leading cause of foodborne illness around the world. Nontyphoidal Salmonella are responsible for an estimated 94 million infections and 155,000 deaths worldwide each year. Of these infections, 86% are estimated to be foodborne. Infection of dairy and beef cattle can lead to contamination of milk and milk products as well as processed beef. Once cattle are infected, Salmonella can be found in many organs of the animals. Peripheral lymph node infections are of particular interest, because these lymph nodes along with hides are the main culprits of meat contamination during processing. Vaccination of production food animals is one of several strategies of prevention and control of Salmonella infections and outbreaks. Vaccination is becoming even more important with the reduction of prophylactic antibiotic use that is driven by an increase in antibiotic resistant bacteria isolated from a variety of food production animals. There are limited commercially available vaccines for cattle that have shown effectiveness, but great strides are being made in this area of research. The vast number of Salmonella serovars with differences in vital virulence factors capable of infecting cattle makes developing vaccines that are cross protective very difficult. This report discusses the known virulence factors of Salmonella, the disease symptoms of bovine salmonellosis, prevention and control strategies, and the development of new vaccines.
Keywords: Salmonella; Bovine; Vaccine